Risk for Maternal Depressive Symptoms and Perceived Stress by Ethnicities in Canada: From Pregnancy Through the Preschool Years. (March 2019) - Dharma, Christoffer; Lefebvre, Diana L.; Lu, Zihang; Lou, Wendy Y. W.; Becker, Allan B.; Mandhane, Piush J.; Turvey, Stuart E.; Moraes, Theo J.; Azad, Meghan B.; Chen, Edith; Elliott, Susan J.; Kozyrskyj, Anita L.; et al.
Objective: Past cross-sectional studies have reported that mothers from ethnic minorities experience higher levels of prenatal and post-partum psychosocial distress compared with mothers from ethnic majorities. However, no studies have examined how the pattern varies longitudinally in a Canadian population of heterogeneous ethnicity. Methods: We analyzed data from 3, 138 mothers participating in the Canadian Healthy Infant Longitudinal Development (CHILD) Study, a longitudinal multi-center study incorporating 10 distinct waves of psychosocial data collection from pregnancy until the index child was aged 5 y. Maternal self-identified ethnicity was grouped as White Caucasian, First Nations, Black, Southeast Asian, East Asian, South Asian, Middle Eastern, Hispanic and mixed ethnicity. We performed a multi-level regression to determine whether mothers of specific minority ethnicities were more likely to experience higher levels of distress (i.e. depressive symptoms and perceived stress) compared to white Caucasian mothers. Results: Mothers self-identifying as Black or First Nations had consistently higher distress scores than mothers from other ethnicities across all data collection times. After adjusting for relevant variables (history of depression, education, household income, marital status, and social support), First Nations mothers had a 20% increase in the mean scores of depressive symptoms compared to White Caucasian Mothers. Conclusions: Increased levels of perinatal and post-partum distress were seen in only some ethnic minority groups. Studies should avoid collapsing all categories into ethnic minority or majority and may need to consider how ethnicity interacts with other sociodemographic factors such as poverty.